Tonic immobility by dogs : a thesis presented in partial fulfilment of the requirements for the degree of Master of Veterinary Science in Veterinary Ethology at Massey University - Ong, Rae Ming (Massey University, 1993)
Tonic immobility (TI) is a state of relative immobility induced by restraint and presumed to function as a terminal defensive reaction. Although TI has been reported in a wide spectrum of species ranging from invertebrates to mammals, there have been very limited studies on TI by dogs. The aim of this thesis was to determine the susceptibility and characteristics of TI in dogs so that the feasibility of using TI as a humane, quick, easily reversible, non-chemical and safe method of restraint for veterinary procedures could be assessed. In an initial survey, 132 dogs were tested twice. Once by inversion and 30s restraint in the lateral position and once with an additional treatment (stroking, scruffing, blanket over head, cuff around ears or light into eyes) during the 30s restraint. Based on the criterion of remaining in the position restrained, without lifting its head off the test surface, for a minimum of 10s after release from restraint, 10 of the 132 dogs (7.6%) exhibited TI. The characteristics of the dogs during TI were similar to those reported in other species, as the dogs remained very still, with the exception of occasional repositioning of heads and limbs, muscle tremors, twitches and paw movements. Swallowing, lip licking, blinking and occasional periods of eye closure were also observed but dogs had their eyes open throughout most of the TI episodes and appeared to be continually monitoring their environment as eye and ear movements, muscle twitches and changes in respiration rate were observed in response to auditory and other stimuli. Many TI episodes were not terminated by intense stimulation such as loud auditory stimuli or physiological testing that included pinching between the dog's toes and inserting a thermometer into the dog's rectum. Respiration rate, heart rate, withdrawal reflexes and temperature were monitored on these dogs. These physiological parameters were all within normal limits. Susceptibility to TI appeared to be a dog effect rather than a technique effect. Timid dogs or dogs that eliminated during testing were more susceptible to TI, indicating that susceptibility may be related to the dog's temperament or fearfulness. It was also found that proestrous bitches were more susceptible to TI than the other dogs. A potentiation effect with repeated testing was observed when the intertrial interval was between 20-80s. No order or carry-over effect was however found when a 3 min intertrial interval was used. No difference in susceptibility to TI was found between techniques but the cuffing technique resulted in longer TI durations than the others. Results should however, be interpreted with caution due to the small number of dogs exhibiting TI. More extensive investigations of the characteristics and physiological changes during TI and the effect of individual variables on TI susceptibility and durations are also required to determine the safety and extent of procedures that may be conducted while dogs are in TI. The results from this initial study are promising as they show that dogs do exhibit TI. The duration, characteristics and physiological changes observed during TI also indicate the potential for using TI as a quick, non-chemical, easily reversible and safe method of restraint in some dogs, for routine clinical examinations or even veterinary procedures.
Keywords: Animal immobilization; Dogs as laboratory animals